The spliceosome as an indicted conspirator in myeloid malignancies - Abdel-Wahab, Omar (2011)
Data from two recent studies of whole-exome sequencing of myelodysplastic syndrome (MDS) suggests spliceosome mutations have clinical relevance. Identifying the impact of these mutations on pre-mRNA splicing and MDS pathogenesis holds promise for targeted modulation of mRNA splicing in MDS.